The Economic Diversity of Immigration Across the United States - Rachel Friedberg; David Jaeger (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
While it is well known that some areas of the United States receive more immigrants than others, less is understood about the extent to which the character of immigration varies as well. There is much broader geographic variation in the skill and demographic composition of immigrants than natives, with important implications for their economic effects. This paper provides a new perspective by focusing on heterogeneity in outcomes such as the share of population growth due to immigration, the presence of immigrant children in schools, and the effect of immigration on the age, sex, language, and educational composition of the local population and workforce.
Keywords: 330